Entrepreneurship Education and Learning for Full Employment - Irmiya, Ruth A.; Tiamiyu, Kehinde A.; Ayuba, Shikdima V. (NIU Journal of Humanities, 2019)
This paper has so far examined entrepreneurship education and learning for full employment with reference to improved government strategies and pragmatic approaches to teaching. Entrepreneurship education as an integral part of innovation and technology enables individuals to champion their cause, arrest the environment for the betterment of standard of living and enhancement of quality of life. Despite the efforts Government is putting behind entrepreneurship education in Nigeria in a bid to reduce unemployment and sustain economic growth, contentment still eludes us. It has been argued that when one is frustrated, one should change approach. It was on this basis that government was asked to provide conducive macroeconomic policy environment, robust entrepreneurship education, protection of intellectual property right, sound financial system, and strong institution. The paper further suggested that Malcolm Knowles’s Andragogy Principles should be adopted during the course of teaching and designing entrepreneurship Instructions. How entrepreneurship education and learning could deliver us from unemployment was equally enumerated. Key words: Entrepreneurship education, learning, andragogy principles, full employment, Nigerian economy